2020
DOI: 10.1136/jitc-2020-000695
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the innate immune barriers to antitumor immunity

Abstract: The immune system evolved for adequate surveillance and killing of pathogens while minimizing host damage, such as due to chronic or exaggerated inflammation and autoimmunity. This is achieved by negative regulators and checkpoints that limit the magnitude and time course of the immune response. Tumor cells often escape immune surveillance and killing. Therefore, disrupting the brakes built into the immune system should effectively boost the anticancer immune response. The success of anti-CTLA4, anti-PD-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 181 publications
(176 reference statements)
1
43
0
Order By: Relevance
“…Regrettably, the mechanism by which these three genes affect the prognosis of patients with OSs is still unclear, and it is worth exploring in the future. We speculate that COCH overexpression may induce the secretion of multiple cytokines and enhance the recruitment of immune cells, leading to the imbalance of the local inflammatory environment of TME and mediating the immune escape of tumor cells [ 59 61 ]. Similarly, MYOM2 overexpression may also mediate the malignant phenotype of tumor cells by affecting the inflammatory response of TME [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regrettably, the mechanism by which these three genes affect the prognosis of patients with OSs is still unclear, and it is worth exploring in the future. We speculate that COCH overexpression may induce the secretion of multiple cytokines and enhance the recruitment of immune cells, leading to the imbalance of the local inflammatory environment of TME and mediating the immune escape of tumor cells [ 59 61 ]. Similarly, MYOM2 overexpression may also mediate the malignant phenotype of tumor cells by affecting the inflammatory response of TME [ 49 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, OSs cells could regulate the recruitment and differentiation of immune infiltrating cells (TIICs) to establish a local immune tolerance environment that was conducive to tumor growth, drug resistance and metastasis. OSs cells also could control the T-lymphocyte responses via the PD-1/PDL-1 system to affect the balance between M1 and M2 macrophage subtypes, then leading to immune tolerance [ 58 , 59 ]. A study used whole genome, T cell receptor sequencing and other methods to analyze the immune status of OSs, and confirmed that there were likely multiple immune-suppressive features in OSs, which might lead to poor response to immune checkpoint inhibitors and neoadjuvant chemotherapy [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing understanding that CAFs play a key role in immunosurveillance in the tumor microenvironment. In parallel, and even earlier, innate immune responses elicited from the surrounding normal cells would cause release of inflammatory mediators necessary for the full-blown immune response [93] . However, in the resulting complex of immune cells both inhibitors and checkpoints are produced and can suppress innate immunity.…”
Section: Inflammation As a Critical Target Of The Cancer Processmentioning
confidence: 99%
“…The repertoire of Shp1 functions is continuously expanding to include the modulation of the tumor microenvironment, thus suggesting new potential therapeutic implications. In recent years cancer immunotherapy, which exploits T-cells to arm the immune system against tumoral cells, has shown promising results based on a multitude of targeting strategies such as immunomodulatory monoclonal antibodies, adoptive cell transfers, high-dose immunostimulatory cytokines, and others (93). Among these, encouraging results have been achieved through the targeting of inhibitory crucial molecules of the antitumor T-cell response such as programmed-cell death 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) (93).…”
Section: Shp1 and Cancer Immunotherapymentioning
confidence: 99%